2016
DOI: 10.3109/14756366.2015.1132709
|View full text |Cite
|
Sign up to set email alerts
|

Two legume defense proteins suppress the mobility of nasopharyngeal carcinoma cells

Abstract: A 16-kDa trypsin inhibitor was isolated from an edible legume using various chromatographic procedures. The protein was unadsorbed on Affi-gel blue gel but adsorbed on DEAE-Sepharose and Mono Q following which media the protein was subsequently subjected to gel filtration on Superdex 75 and a final 21-fold purification was achieved. This trypsin inhibitor showed remarkable pH and thermal stability. Its inhibitory activity was impaired in the presence of 1 mM dithiothreitol. The anti-proliferative and anti-mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Lectins are widespread in nature, and most of them have been isolated and characterized from Fabaceae, Gramineae, and Lamiaceae families, among others [47,48]. Those lectins have been related to insect defense mechanisms, storage proteins, carbohydrate transport, mechanisms of physiological regulation, and mitogenic stimulation processes [49][50][51][52][53][54][55]. The ability of the nitrogen-fixing bacteria rhizobia to form a symbiotic relationship with legumes, in which plant root lectins are involved, is well known.…”
Section: Fabaceae (Legume) and Lamiaceae (Mint) Lectinsmentioning
confidence: 99%
“…Lectins are widespread in nature, and most of them have been isolated and characterized from Fabaceae, Gramineae, and Lamiaceae families, among others [47,48]. Those lectins have been related to insect defense mechanisms, storage proteins, carbohydrate transport, mechanisms of physiological regulation, and mitogenic stimulation processes [49][50][51][52][53][54][55]. The ability of the nitrogen-fixing bacteria rhizobia to form a symbiotic relationship with legumes, in which plant root lectins are involved, is well known.…”
Section: Fabaceae (Legume) and Lamiaceae (Mint) Lectinsmentioning
confidence: 99%
“…This is due to intestinal proteolysis inhibition, meaning relevant endogenous sulfur amino acid losses, affecting the biological value and bioavailability of nutrients (Coscueta et al, ). However, positive physiological effects such as carcinogenesis suppression and anti‐inflammatory activity in several in vitro and animal studies were associated with soy products found in the diet, Bowman‐Birk‐Inhibitor (BBI) PI type being the main one involved (Dan & Ng, ; Gemede & Ratta, ).…”
Section: Introductionmentioning
confidence: 99%